Dry mass yield from sainfoin in binary mixtures with ryegrass and cocksfoot - Vasilev E. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
A field trial under non-irrigated conditions was carried out in Central North Bulgaria. Two sainfoin populations, cultivar 'Jubilejna' and the new selected No. 239 were tested in pure stands, and in binary mixtures with perennial ryegrass and cocksfoot under cutting regime of utilization. Sainfoin had a bigger portion in mixtures with ryegrass in second and third cut as compared to the mixture with cocksfoot. The mixtures were less infested than pure sainfoin, but the mixtures with ryegrass were more infested than those with cocksfoot. On average for three years the dry mass yield from sainfoin No. 239 was 20% higher than that from sainfoin 'Jubilejna' in pure stands, and 19% higher on average for mixtures with grasses. There was no difference in the average annual dry mass yield from pure sainfoin stands as compared to those from mixtures, but considering weed proportion, the mixtures showed advantages.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)